Prioritas Strategi Pengembangan Agribisnis Selada Hidroponik (SWOT–AHP) di Kebumen Indonesia - Ma'dan Sururi; Dwi Aulia Puspitaningrum (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Kebun Sayur 24 is a hydroponic lettuce agribusiness located in Kebumen Regency that faces several problems, including production fluctuations, limited human resources competence, and underutilization of digital marketing. This research aims to examine organizational factors and environmental influences, evaluate alternative business development strategies, and determine the most prioritized strategic option. The research was conducted on Kebun Sayur 24 as the study subject, with purposive sampling involving three respondents: the owner, production staff, and marketing staff. Data were collected through observational methods, interviews, group discussions, questionnaire surveys, and document analysis. The analysis employed a series of strategic management tools such as the internal factor evaluation, external factor evaluation, the internal external (IE) matrix, SWOT analysis, and the analytic hierarchy process (AHP). According to the analytical results, Kebun Sayur 24 obtained an IFE score of 3.004 and an EFE score of 2.547, suggesting that the enterprise holds a comparatively strong position in both its internal capabilities and external environment. The AHP analysis yields a priority weight of 0.374 and a Consistency Ratio (CR) of 0.02, indicating good consistency. The results of the research show alternative strategies for Kebun Sayur 24 generated by the SWOT matrix with the highest scores were the S-O (Strength-Opportunity) strategies, included establishing partnerships with marketing partners in need of hydroponic lettuce supplies; developing hydroponic products beyond just lettuce; investing in IoT-based hydroponic technology with applications; and creating promotions with a campaign highlighting hydroponic lettuce as a quality, healthy, and environmentally friendly product. The AHP analysis confirmed that the top-priority strategy is to create promotions with a campaign that emphasizes hydroponic lettuce as a high-quality, healthy, and environmentally friendly product. As a recommendation, Kebun Sayur 24 should optimize its digital marketing and expand its market reach to strengthen competitiveness.